Risk factors of neonatal mortality in Maternal Perinatal Installation Dr. Sardjito Hospital, Yogyakarta - Tri Yanti, Tri Yanti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2004)
Background: Neonatal mortality rate in Indonesia is still relatively high. There are many factors influencing the outcome of neonatal life. Identifying the risk factors is important to prevent neonatal mortality. The intervention could be done by avoiding or minimizing the risk factors.Objective: To know the risk factors of neonatal mortality in Maternal Perinatal Installation, Dr. Sardjito Hospital Yogyakarta, and the contribution of these risk factors.Methods: One hundred and twenty three newborns in Maternal Perinatal Installation Dr Sardjito Hospital from 1 February 2003 to 28 February 2004 were enrolled in this study, consisting of 41 infants birth alive and all died during hospitalization, and 82 infants alive when discharged from the hospital as control. The data was taken from medical records. Cases were infants those died and control were infants alive when discharged from hospital, and then risk factors were identified.Result: The risk factors that significantly related to neonatal mortality in univariate analysis were sepsis (OR=4.26; 95%C1:1.9-9.4), prematurity (OR=3.26; 95%C1:1.5-7.2), low birth weight (OR =3.41; 95%C1:1.6-7.5), major congenital anomaly (OR =4.29; 95%C1:1.6-11.5), low Apgar score at 5 minute (OR 4.68; 95% CI:1.8-11.9) and hyalin membrane disease (OR =12.90; 95% C1:2.7-62.3). By multivariate analysis, in order of higher contribution, major congenital anomaly (OR =34.80; 95% C1:6.7-182.2), hyalin membran disease (OR =15.00; 95% C1:2.3-96.5), low Apgar score at 5 minute (OR=9.16; 95% C1:1.8-48.0), and sepsis (OR 6.04; 95% C1:1.9-18.9) were significantly related to neonatal mortality. Conclusion: Major congenital anomaly, hyalin membrane disease, sepsis neonatorum and low Apgar score at 5 minute were risk factors of neonatal mortality.Key words: neonatal mortality - sepsis neonatorum - low birth weight - major congenital anomaly - low Apgar score at 5 minute - hyalin membrane disease.